Possible Involvement of Mitochondrial Dysfunction and Oxidative Stress in a Cellular Model of NAFLD Progression Induced by Benzo[a]pyrene/Ethanol CoExposure. (26th July 2018) - Bucher, Simon; Le Guillou, Dounia; Allard, Julien; Pinon, Grégory; Begriche, Karima; Tête, Arnaud; Sergent, Odile; Lagadic-Gossmann, Dominique; Fromenty, Bernard
Abstract : Exposure to xenobiotics could favor the transition of nonalcoholic fatty liver (NAFL) to nonalcoholic steatohepatitis in obese patients. Recently, we showed in different models of NAFL that benzo[a]pyrene (B[a]P) and ethanol coexposure induced a steatohepatitis-like state. One model was HepaRG cells incubated with stearate and oleate for 2 weeks. In the present study, we wished to determine in this model whether mitochondrial dysfunction and reactive oxygen species (ROS) overproduction could be involved in the occurrence of this steatohepatitis-like state. CRISPR/Cas9-modified cells were also used to specify the role of aryl hydrocarbon receptor (AhR), which is potently activated by B[a]P. Thus, nonsteatotic and steatotic HepaRG cells were treated with B[a]P, ethanol, or both molecules for 2 weeks. B[a]P/ethanol coexposure reduced mitochondrial respiratory chain activity, mitochondrial respiration, and mitochondrial DNA levels and induced ROS overproduction in steatotic HepaRG cells. These deleterious effects were less marked or absent in steatotic cells treated with B[a]P alone or ethanol alone and in nonsteatotic cells treated with B[a]P/ethanol. Our study also disclosed that B[a]P/ethanol-induced impairment of mitochondrial respiration was dependent on AhR activation. Hence, mitochondrial dysfunction and ROS generation could explain the occurrence of a steatohepatitis-like state in steatotic HepaRG cells exposed to B[a]P and ethanol.